The Supervisory Function of the Harbormaster’s Office at Port Terminal Facilities Based on Law No. 17 of 2008 on Shipping. - Yusdin; L.M. Ricard Zeldi Putra; Samsul (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
The sea is the boundary of a country with another country with a boundary point determined through bilateral or multilateral extradition which means it is also the limit of a country's power, as far as the outer line of its territory. The purpose of this study was to determine how the role of supervision of the Port Authority in the safety of shipping security and to determine the constraints of the role of the Port Authority in law enforcement and supervision of shipping security safety in the Office of the Port Authority and Class II Baubau. Port supervision is very important because the security and safety of shipping is already his job. The actions taken are in order to increase security and safety supervision on matters related to shipping. The supervisory duties carried out by the Syahbandar in the framework of regulating the facilities and infrastructure for the implementation of sea transportation operations are very important. Syahbandar in his duty must also ensure the awareness of the government of sea transportation services such as companies, ship owners, ship crews to obey the laws and regulations in force in the field of shipping safety which is generally still low. Kesyahbandaran office and Port Authority Class II Babubau is a state of fulfillment peryatan security and safety related to transport in the waters, ports and Maritime Environment (Law of the Republic of Indonesia No. 17 of 2008 on shipping Article (1) paragraph (32). Security and safety is the main thing in transportation, not only national scope, also including international. According to the law of the Republic of Indonesia No. 17 of 2008 on shipping Article (17), the safety and security of new water transportation can occur when the requirements of ship's seaworthiness and navigation are met.